A NEW PERSPECTIVE ON HUMAN CAPITAL THEORY: ANALYSIS OF SHORT-TERM BENEFITS THROUGH THE CONTRIBUTION OF CHILDREN TO THE APPROPRIATION OF ICTS BY THEIR PARENTS IN PORTO-NOVO, BENIN - GAGLOZOUN, ALPHONSE; ABALOT, EMILE JULES; DAKPO, PASCAL CODJO (My University, 2017)
This study aims at highlighting the contribution of children to the appropriation and / or use of ICT by their parents, through the prism of analysis of the short-term benefits of investments in human capital as postulated in the studies of Gaglozoun (2008, 2012). In this context, we formulated the following hypothesis: "The parents of the area of Porto-Novo, civil servant, have recourse to the help of their children who are still on the benches for the use of ICTs". After collecting data from a sample of 130 individuals (110 pupils and 20 parents) by means of a questionnaire and an interview grid addressed to parents (20), the conclusions of our analyzes allow us to suggest that school children support their parents, in the appropriation or use of ICTs. Indeed, it is noted at the end of the study that the parents use their children to input text, slide presentations, use of internet, programs and reception of calls on their cell phones etc. These results, therefore, allow us to postulate that these parents derive substantial benefits from their children's support for their production as civil servant, which would help to improve their household income. These conclusions validate our hypothesis to some extent and corroborate the findings of the Gaglozoun studies (op.cit) that human capital investments can produce short-term benefits and that it is useful to take into account children as an important variable in the assessment grid of sources of human capital acquisition.
Keywords: Human capital; profits; short term; parents.